Functional Connections in the Human Cerebral Cortex at Repetitive Flexions and Extensions of the Fingers - Dornowski, M.; Mishchenko, V. S.; Gorkovenko, A. V. (Neurophysiology (New York), 2018)
In 10 subjects, EEGs were recorded during realization of repetitive movements of the fingers of the dominant hand and production of the static efforts by the fingers. The test included four stages: resting state, the maintenance of the fingers in the maximally extended fingers and those squeezed into a fist, and repetitive flexions/extensions of the fingers. Values of the spectral power of the α and β EEG rhythms and levels of coherence of oscillations in different leads were measured. As was found, repetitive movements of the fingers are accompanied by significant increases in values of the hyperbolic coherence spectrum between a number of the central and frontal leads of the neocortex. The patterns of the respective changes for the α and β rhythms significantly differed from each other. It is concluded that the control of repetitive finger movements is not based on a mechanism of the central pattern generators; such finger movements should be more adequately interpreted as a consequence of the discrete voluntary movements.